Penyuluhan Dan Edukasi Kesehatan Kepada Masyarakat Yang Terdampak Banjir Kecamatan Tukka Kabupaten Tapanuli Tengah - Sihotang, Delita; Batubara, Muhammad Iqbal; Panggabean, Nanda Pratama; Matondang, Safran (CV. Devi Tara Innovations, 2026)
Indonesia is a disaster-prone country, particularly vulnerable to flooding, due to its location at the convergence of three tectonic plates and its high rainfall intensity. According to data from the National Disaster Management Agency (BNPB), floods are the most frequently occurring disasters and cause significant impacts on health, the economy, and the environment. Contributing factors include extreme rainfall, inadequate drainage systems, and the reduction of water catchment areas. Therefore, disaster mitigation efforts are essential to reduce risks and impacts. This community service activity was conducted in Tukka District, Central Tapanuli Regency, which was experiencing flooding at the time of implementation. The objective was to increase community knowledge regarding flood disaster mitigation through health education. The methods employed included interactive lectures, discussions, and the distribution of leaflets containing information on mitigation measures before, during, and after flooding. The results indicated an improvement in community understanding and attitudes toward flood preparedness. Participants showed high enthusiasm during the educational sessions, actively engaged in discussions, and demonstrated an understanding of the importance of community involvement in disaster prevention. Support from the sub-district government further strengthened the success of this activity. Overall, this community service program successfully enhanced awareness and preparedness among the residents of Tukka District in facing flood disasters and strengthened cross-sector collaboration to build a disaster-resilient community.